Band gap adjustable gallium nitride array preparation method based on quantum dot fusion

Through the method based on quantum dot melting, liquid phase assembly and high-temperature melting using silicon column templates, a single-crystal pattern with adjustable bandgap was successfully prepared, solving the problems of high-cost, complex operations and toxic substance use in the prior art, and realizing green and low-cost single-crystal patterning technology of gallium nitride is achieved.

CN119530945APending Publication Date: 2025-02-28BEIJING INST OF FUTURE SCI & TECH ON BIOINSPIRED INTERFACE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456635.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing gallium nitride single crystal patterning technology has problems such as high cost, expensive equipment investment, complex operating steps, and strict demand for precise environmental control. Traditional quantum dots contain toxic heavy metal cadmium, which limits its application areas.

Method used

A method based on quantum dot melting is used to prepare a bandgap-adjusted gallium nitride array. By mixing solvent, anhydrous gallium chloride and organic ligand under vacuum conditions, adding a nitrogen source to form gallium nitride quantum dots, and a silicon column template is prepared by photolithography for liquid phase assembly and high-temperature melting, the preparation of gallium nitride single crystal pattern is achieved.

Benefits of technology

It realizes green and low-cost, in-situ growth, and adjustable band gap after doping, which reduces equipment investment and operation complexity, avoids the use of toxic heavy metals, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530945A_ABST
    Figure CN119530945A_ABST
Patent Text Reader

Abstract

The invention provides a quantum dot fusion-based band gap-adjustable gallium nitride array preparation method, which comprises the following steps of: synthesizing gallium nitride quantum dots, inducing a quantum dot liquid phase to assemble into a superlattice structure array in a capillary liquid bridge confinement in a silicon column template, and fusing the superlattice structure array in the silicon column template in a high-temperature confinement manner to obtain the quantum dot fusion-based band gap-adjustable gallium nitride array. And after annealing, stripping from the template to prepare the gallium nitride single crystal patterned array growing on the substrate. The gallium nitride quantum dots with different doping proportions and adjustable band gaps can be prepared by introducing indium salt or zinc salt in the synthesis process; along with the evaporation of the gallium nitride quantum dot dispersion solution solvent, the particles are gradually and orderly accumulated under the action of capillary force, Laplace pressure and continuous Malangori flow, and the long-range ordered gallium nitride quantum dot superlattice array is prepared. The organic ligands are carbonized and decomposed at the melting temperature, and the gallium nitride quantum dots are effectively fused after the ligands are eliminated; the method has the advantages that the operation is convenient, the cost is low, and the materials are green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical technology, and in particular to a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting. Background Art

[0002] As a third-generation semiconductor, gallium nitride (GaN) has the characteristics of wide direct band gap, low dielectric constant, high breakdown electric field, high electron mobility, high thermal conductivity, high electron saturation velocity, nonlinear optical activity, etc., which can meet the requirements of high frequency, high efficiency, high power, high temperature, radiation resistance, heat resistance, acid resistance, high-density integration, etc. Patterned gallium nitride single crystals that can be designed and controlled by micro-nano processing have broad application prospects in lasers, photonic integrated chips, LEDs and other fields.

[0003] At present, MOCVD, HVPE, ammonothermal method and solvent method are commonly used to prepare GaN single crystals. These methods are relatively mature, but the conditions are harsh and have high requirements for raw materials and equipment. In order to construct GaN optoelectronic devices, high-quality GaN patterned arrays are required. Commonly used GaN patterning methods include femtosecond laser etching and ICP etching, which are costly, slow etching rates, and prone to defects. On the other hand, traditional quantum dots usually contain toxic heavy metal cadmium, which limits their application areas. The preparation of non-toxic and cadmium-free GaN quantum dots can reduce the impact on the environment and health. Furthermore, as the performance standards of electronic and optoelectronic devices continue to rise, doping technology that regulates the band gap of GaN by changing the type and proportion of doped metals has become a key means to improve the efficiency and performance of these devices. Although methods such as chemical vapor deposition, ion implantation and plasma doping have proven their effectiveness in laboratories and small-scale production, they still face many challenges, including high equipment investment, complex operating steps, and demanding requirements for precise environmental control.

[0004] Therefore, there is an urgent need to develop a green, low-cost, in-situ grown, bandgap-adjustable GaN single crystal patterning technology. Summary of the invention

[0005] The present invention aims to solve the problem of patterning of gallium nitride single crystals and provides a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting.

[0006] The present invention provides a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting, comprising the following steps:

[0007] S1. Add a solvent, anhydrous gallium chloride and an organic ligand into a three-necked flask for vacuum degassing, heat the mixture using a liquid phase assembly drying device, inject a nitrogen source into the three-necked flask to obtain gallium nitride quantum dots, and then wash the mixture with a dispersion solvent to obtain a liquid phase assembled gallium nitride quantum dot dispersion;

[0008] S2, preparing a silicon column template by photolithography, wherein the silicon column sidewalls of the silicon column template are hydrophobic and the top surface is hydrophilic;

[0009] S3, dropping the liquid-phase assembled gallium nitride quantum dot dispersion onto the surface of the silicon pillar template, and covering the surface of the silicon pillar template with a substrate to obtain a template induction device, and placing the template induction device at room temperature to evaporate the dispersion solvent in the liquid-phase assembled gallium nitride quantum dot dispersion to obtain a gallium nitride quantum dot superlattice array;

[0010] S4, placing the GaN quantum dot superlattice array in a high-temperature melting device filled with a nitrogen atmosphere to increase the temperature so that the organic ligands are carbonized and decomposed, and the GaN quantum dots in the GaN quantum dot superlattice array are fused, and then cooled to room temperature;

[0011] S5. The silicon pillar template is peeled off from the substrate to obtain a gallium nitride single crystal pattern with the same shape as the micro-pillar template on the substrate, and a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting is completed.

[0012] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S1, the solvent is octadecene, the organic ligand is stearic acid, the nitrogen source is a n-hexane solution of lithium bis(trimethylsilyl)amide, and the dispersion solvent is n-hexane or n-octane or acetone;

[0013] The three-necked flask used an argon atmosphere and was located in an anhydrous and oxygen-free device, which included a glove box and a double-row tube.

[0014] The invention discloses a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting. As a preferred method, octadecene is placed in a three-necked flask under anhydrous and oxygen-free condition, vacuum degassed, and then anhydrous gallium chloride and an organic ligand are added. The mixture is stirred and dissolved while vacuum degassed. After heating, a n-hexane solution of lithium bis(trimethylsilyl)amide is injected, and heating and stirring are continued to react until the reaction is complete, the heat source is removed, and the reaction is quenched. After the temperature is restored to room temperature, a dispersion solvent is added, centrifuged, the supernatant is taken, the dispersion solvent is added, and centrifuged again to obtain a white precipitate, which is gallium nitride quantum dots including ligands. The white precipitate is dispersed in a dispersion solvent, washed, and then dispersed in a dispersion solvent to obtain a liquid-phase assembled gallium nitride quantum dot dispersion.

[0015] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S1, indium or zinc is doped into the gallium nitride quantum dots by adding indium salt or zinc salt into a three-necked flask, and the bandgap is adjusted by adjusting the proportion of the added indium salt or zinc salt.

[0016] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred mode, in step S1, under anhydrous and oxygen-free conditions, 5-10 mL of octadecene is placed in a three-necked flask, and vacuum degassing is performed for 2 hours to remove water and oxygen in the solvent, 0.5-1.0 mmol of anhydrous gallium chloride and 1.5-3.0 mmol of stearic acid are added to the three-necked flask, and vacuum degassing is continued for 2 hours while stirring and dissolving; after heating to 220-300° C. at 10° C. / min, 1-2 mL of 1.5 M lithium bistrimethylsilylamide n-hexane solution is quickly injected into the three-necked flask, and the heating and stirring reaction is continued for 10-100 minutes, the heat source is removed, and the reaction is cooled with ice water to quench the reaction. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 minutes. The supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 minutes. The white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 minutes. The n-hexane and ethanol were added and washed twice. Finally, the obtained white precipitate was dispersed in n-hexane to obtain a n-hexane dispersion of gallium nitride quantum dots.

[0017] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S1, 0.5-1.0 mmol anhydrous gallium chloride, 0.1-0.5 mmol indium nitrate and 1.5-3.0 mmol stearic acid are added to a three-necked flask, step S1 obtains an indium-doped gallium nitride quantum dot n-hexane dispersion, step S3 obtains an indium-doped gallium nitride quantum dot superlattice array, and step S5 obtains an indium-doped gallium nitride pattern.

[0018] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S1, 0.5-1.0 mmol anhydrous gallium chloride, 0.1-0.5 mmol zinc stearate and 1.5-3.0 mmol stearic acid are added to a three-necked flask, step S1 obtains a zinc-doped gallium nitride quantum dot n-hexane dispersion, step S3 obtains a zinc-doped gallium nitride quantum dot superlattice array, and step S5 obtains a zinc-doped gallium nitride pattern.

[0019] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S2, the silicon column spacing of the silicon column template is 1-100μm, the width is 1-100μm, and the height is 10-100μm. The shape of the silicon columns is a straight line, a rectangle, a triangle, or a ring, and the silicon columns are arranged in an array.

[0020] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred embodiment, in step S3, the substrate is any one of the following: silicon wafer, sapphire, quartz wafer, silicon dioxide wafer, gold wafer, silver wafer and platinum wafer, and the substrate is ultrasonicated for 20 minutes in deionized water, ethanol, acetone and isopropanol respectively before use, and dried with nitrogen for standby use;

[0021] The volume of the liquid-phase assembled gallium nitride quantum dot dispersion is 5-20 μL, and the evaporation temperature range is: 20-60°C.

[0022] The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting described in the present invention is, as a preferred mode, in step S4, without disassembling the template induction device, placing the gallium nitride quantum dot superlattice array in a high-temperature melting device filled with nitrogen atmosphere, heating to 900-1100°C at 10°C / min, keeping the temperature for 60-90min, and finally cooling to room temperature at 5°C / min;

[0023] The liquid phase assembly drying device and the high temperature melting device are any one of the following: a heating sheet, a heating plate, a vacuum oven and a tube furnace.

[0024] The present invention provides a method for assembling a long-range ordered gallium nitride quantum dot superlattice structure array and melting it into a gallium nitride single crystal pattern, comprising the following steps: synthesizing gallium nitride quantum dots; confining the quantum dots into a superlattice structure array by capillary liquid bridges in a silicon pillar template; confining the superlattice array by high temperature confinement of the silicon pillar template; and peeling it off the template after annealing to obtain a gallium nitride single crystal patterned array grown on a substrate.

[0025] The silicon column template has a silicon column spacing of 1-100 μm, a width of 1-100 μm, and a height of 10-100 μm. The shape of the silicon column is not limited to straight lines, rectangles, triangles, and circles.

[0026] The substrate is selected from one of silicon wafer, sapphire, quartz wafer, silicon dioxide wafer, gold wafer, silver wafer and platinum wafer. Before use, the substrate is ultrasonicated for 20 minutes in deionized water, ethanol, acetone and isopropanol respectively, and dried with nitrogen for later use.

[0027] The synthesis of gallium nitride quantum dots uses one of the water-free and oxygen-free devices such as a glove box and a double-row tube.

[0028] The synthesis conditions of gallium nitride quantum dots are carried out in an argon atmosphere and heated at 240-280°C.

[0029] The types of GaN quantum dot dispersion solvents used for liquid phase assembly are not limited to n-hexane, n-octane, acetone, etc.

[0030] The volume of the dispersion liquid for assembling the superlattice by the silicon pillar template confined liquid phase is 5-20 μL, and the temperature is selected at 20-60°C.

[0031] The liquid phase assembly drying device and the high temperature melting device use one of the heating devices such as a heating sheet, a heating plate, a vacuum oven and a tube furnace.

[0032] The heating and cooling procedures for heating and fusing the GaN quantum dot superlattice array include: heating rate 10-15°C / min, keeping warm for 30-90min, cooling 5-10°C / min, and taking out and peeling off after cooling to room temperature.

[0033] The present invention is a method for assembling a long-range ordered GaN quantum dot superlattice structure array and melting it into a GaN single crystal pattern:

[0034] 1) Synthesis of GaN quantum dots. A green and mild GaN quantum dot synthesis method is used to adjust the reaction conditions and washing methods to synthesize monodisperse GaN quantum dots with uniform particle size and clear edges. In addition, GaN quantum dots with adjustable band gaps at different doping ratios are prepared by introducing indium salts or zinc salts during the synthesis process. The synthesized quantum dots maintain uniformity and fluidity after being dispersed in the solvent, meeting the requirements of liquid phase assembly;

[0035] The reaction equation is as follows:

[0036]

[0037] 2) The capillary liquid bridge in the micro-column template induces the quantum dots to assemble into a superlattice structure array. The GaN quantum dot dispersion is added dropwise between the micro-column template and the substrate to form a continuous liquid film. As the solvent evaporates, it is divided into independent liquid bridges under the action of capillary force and Laplace pressure. The dewetting continues. Under the continuous Marangoni flow in each independent liquid bridge, the particles gradually accumulate in an orderly manner to prepare a long-range ordered GaN quantum dot superlattice array.

[0038] 3) Micro-pillar template high temperature confined melting superlattice array. Under the confined conditions of the micro-pillar template, the melting temperature is adjusted, the organic ligands are carbonized and decomposed at high temperature, and the gallium nitride quantum dots are effectively fused after the ligands are eliminated;

[0039] 4) After annealing, it is peeled off from the template to obtain a gallium nitride single crystal pattern array. The heating and cooling and annealing procedures and conditions are controlled to reduce the generation of cracks and defects. Since the surface of the silicon pillar template has an ordered microstructure, it is easy to peel off the silicon pillar template directly after cooling, and a gallium nitride single crystal pattern consistent with the shape of the micro-pillar template is obtained on the substrate. The gallium nitride superlattice and single crystal array prepared by the method provided by the present invention can realize subsequent integrated applications, and arrays of different sizes can be prepared by designing different templates. The method is simple to operate, low cost, and green materials, providing a new idea for realizing industrialization.

[0040] The present invention has the following advantages:

[0041] The preparation method of assembling a gallium nitride quantum dot superlattice structure array and melting it into a gallium nitride single crystal pattern provided by the present invention is easy to operate, low in cost, and uses green materials, does not require expensive equipment, and the template, substrate and other materials in the preparation method can be reused, and has the potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1a A flow chart of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting and a superlattice structure array assembly process;

[0043] Figure 1b A GaN melt patterning preparation flow chart of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0044] Figure 2 A schematic diagram of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting and a process for synthesizing gallium nitride quantum dots by hot injection;

[0045] Figure 3 Transmission electron microscope image of the gallium nitride quantum dots synthesized in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0046] Figure 4 The X-ray diffraction pattern of the gallium nitride quantum dots in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0047] Figure 5 PL spectra of gallium nitride and indium and zinc doped gallium nitride quantum dots with adjustable band gap in Examples 1 to 5 of a method for preparing a gallium nitride array with adjustable band gap based on quantum dot melting;

[0048] Figure 6 This is a macroscopic optical microscope image of gallium nitride quantum dots assembled into a superlattice structure array in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0049] Figure 7 A transmission electron microscope image of a single micrometer wire in a gallium nitride quantum dot superlattice array in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting and a uniform morphology image after partial magnification;

[0050] Figure 8 An optical microscope image of a gallium nitride quantum dot superlattice structure array assembled by micropillar array induction in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0051] Fig. 9An X-ray diffraction diagram of a gallium nitride single crystal pattern array prepared after melting the gallium nitride quantum dot superlattice array in Example 1 of a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting;

[0052] Fig.10 A Raman spectrum of a gallium nitride pattern array prepared after melting the gallium nitride quantum dot superlattice array in Example 1 of a method for preparing a bandgap-adjustable gallium nitride array based on quantum dot melting;

[0053] Fig.11 The scanning electron microscope and energy spectrum diagram of the gallium nitride single crystal pattern array prepared after the gallium nitride quantum dot superlattice array is melted in Example 1 of a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting;

[0054] Fig.12 The scanning electron microscope and energy spectrum diagram of the indium-doped gallium nitride crystal pattern array prepared after the 25% indium-doped gallium nitride quantum dot superlattice array is melted in Example 2 of a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting;

[0055] Fig.13 The present invention provides a scanning electron microscope and energy spectrum diagram of an indium-doped gallium nitride crystal pattern array prepared by melting a 25% zinc-doped gallium nitride quantum dot superlattice array in Example 4 of a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting. DETAILED DESCRIPTION

[0056] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0057] Example 1

[0058] like Figure 1a-1b As shown, a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting comprises the following steps:

[0059] 1) Synthesis of monodisperse GaN colloidal quantum dots. Under anhydrous and oxygen-free conditions, 5 mL of octadecene was placed in a three-necked flask and vacuum degassed for 2 h to remove water and oxygen from the solvent. 0.5 mmol of anhydrous gallium chloride and 1.5 mmol of stearic acid were added to the three-necked flask and vacuum degassed for 2 h while stirring and dissolving. After heating to 260 ° C at 10 ° C / min, 1 mL of 1.5 M lithium bistrimethylsilylamide in n-hexane solution was quickly injected into the three-necked flask, and the reaction was continued for 30 min by heating and stirring. The heat source was removed and cooled with ice water to quench the reaction. After the temperature returned to room temperature, the resulting liquid was added to n-hexane and centrifuged at 8000 rpm for 3 min, the supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 min, the white precipitate was dispersed in n-hexane, ethanol was added and centrifuged at 9000 rpm for 3 min, and n-hexane and ethanol were added to wash twice, and finally the resulting white precipitate was dispersed in n-hexane.

[0060] The synthesis process is as follows Figure 2 As shown, the reaction process is as follows:

[0061] GaCl3+[(CH3)3Si]2NLi(LiHMDS)→GaN+2(CH3)3SiCl+LiCl;

[0062] The morphology of synthesized GaN quantum dots is shown in Figure 3 As shown, it can be seen that the GaN quantum dots have uniform particle size, regular shape and clear edges; the X-ray diffraction results are as follows Figure 4 As shown, it can be seen that GaN quantum dots have characteristic peaks of hexagonal GaN; Figure 5 As shown, the peak at 392 nm represents the PL data of GaN quantum dots.

[0063] 2) A silicon column template was prepared by photolithography, with a single silicon column having a width of 2 μm and a spacing of 16 μm. FAS modification was used to make the sidewalls of the silicon column template hydrophobic and the top hydrophilic.

[0064] 3) 15 μL of 100 mg / mL GaN quantum dot n-hexane dispersion was added to the surface of the silicon pillar template, covered with a silicon wafer substrate, and the entire template induction device was placed at room temperature to allow the solvent to evaporate naturally. The microscope image of the GaN quantum dot superlattice array obtained after evaporation is shown in Figure 2. Figure 6 The transmission electron microscope of a single micrometer wire and the uniform morphology after partial magnification are shown in Figure 7 As shown, different positions of the GaN quantum dot superlattice array show highly ordered quantum dot superlattice structures.

[0065] 4) Without disassembling the device of the above steps, the unpeeled GaN quantum dot superlattice array with silicon pillar template is placed in a tubular furnace filled with nitrogen atmosphere, and the temperature is raised to 1000°C at 10°C / min, kept at this temperature for 60 minutes, and the GaN quantum dots in the array are gradually fused, and finally cooled to room temperature at 5°C / min.

[0066] 5) The template is peeled off from the substrate, and a GaN single crystal pattern consistent with the shape of the micro-pillar template is obtained on the silicon wafer substrate. Figure 8 As shown in Figure 1, it can be seen that the GaN quantum dot superlattice structure array has accurate position, clear morphology edges, and high order. The X-ray diffraction data of the GaN single crystal pattern is shown in Figure 1. Fig. 9 As shown in Figure 1, the characteristic peaks show that the GaN single crystal array has a hexagonal phase structure. The Raman spectrum of the GaN single crystal pattern array is shown in Figure 1. Fig.10 The scanning electron microscope image and energy spectrum data of the GaN single crystal pattern array are shown in Fig.11 As shown, the scanning electron microscope image shows that the gallium nitride single crystal array has uniform morphology, high order, and accurate position, and the energy spectrum data shows that the elements are evenly distributed.

[0067] Example 2

[0068] like Figure 1a-1b As shown, a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting comprises the following steps:

[0069] 1) Synthesis of indium-doped (25%) gallium nitride colloidal quantum dots. Under anhydrous and oxygen-free conditions, 5 mL of octadecene was placed in a three-necked flask and vacuum degassed for 2 h to remove water and oxygen in the solvent. 0.5 mmol of anhydrous gallium chloride, 0.17 mmol of indium nitrate and 1.5 mmol of stearic acid were added to the three-necked flask and vacuum degassed for 2 h while stirring and dissolving. After heating to 240 ° C at 10 ° C / min, 1 mL of 1.5 M lithium bis (trimethylsilyl) amide in n-hexane solution was quickly injected into the three-necked flask, and the reaction was continued by heating and stirring for 20 min, and the heat source was removed and cooled with ice water to quench the reaction. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 min, the supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 min, the white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 min, and n-hexane and ethanol were added to wash twice, and finally the obtained white precipitate was dispersed in n-hexane;

[0070] The synthesis process is as follows Figure 2 As shown, the reaction process is as follows:

[0071] In(NO3)3+GaCl3+[(CH3)3Si]2NLi(LiHMDS)→InGaN+2(CH3)3SiCl+LiCl

[0072] like Figure 5 As shown, the peak at 469nm is the PL data of 25% indium-doped gallium nitride quantum dots.

[0073] 2) A silicon column template was prepared by photolithography, with a single silicon column having a width of 2 μm and a spacing of 16 μm. FAS modification was used to make the sidewalls of the silicon column template hydrophobic and the top hydrophilic.

[0074] 3) 15 μL of 100 mg / mL indium-doped gallium nitride quantum dot n-hexane dispersion was added to the surface of the silicon pillar template, covered with a silicon wafer substrate, and the entire template induction device was placed at room temperature to allow the solvent to evaporate naturally. After evaporation, an indium gallium nitride quantum dot superlattice array was obtained.

[0075] 4) Without disassembling the device of the above steps, the unpeeled indium-doped gallium nitride quantum dot superlattice array with silicon pillar template is placed in a tubular furnace filled with nitrogen atmosphere, and the temperature is raised to 950°C at 10°C / min and kept at this temperature for 45 minutes. The indium-doped gallium nitride quantum dots in the array gradually fuse, and finally the temperature is cooled to room temperature at 5°C / min.

[0076] 5) The template and the substrate are peeled off to obtain an indium-doped gallium nitride pattern on the silicon wafer substrate that is consistent with the shape of the micro-pillar template. The scanning electron microscope and energy spectrum are as follows: Fig.12 As shown, the scanning electron microscope photos show that the array has uniform morphology, high order, and accurate position. The energy spectrum data show that the elements are evenly distributed and indium is successfully doped.

[0077] Example 3

[0078] like Figure 1a-1b As shown, a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting comprises the following steps:

[0079] 1) Synthesis of indium-doped (50%) gallium nitride colloidal quantum dots. Under anhydrous and oxygen-free conditions, 5 mL of octadecene was placed in a three-necked flask and vacuum degassed for 2 h to remove water and oxygen in the solvent. 0.5 mmol of anhydrous gallium chloride, 0.5 mmol of indium nitrate and 1.5 mmol of stearic acid were added to the three-necked flask and vacuum degassed for 2 h while stirring and dissolving. After heating to 240 ° C at 10 ° C / min, 1 mL of 1.5 M lithium bistrimethylsilylamide in n-hexane solution was quickly injected into the three-necked flask, and the reaction was continued by heating and stirring for 20 min, and the heat source was removed and cooled with ice water to quench the reaction. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 min, the supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 min, the white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 min, and n-hexane and ethanol were added to wash twice, and finally the obtained white precipitate was dispersed in n-hexane;

[0080] The synthesis process is as follows Figure 2 As shown, the reaction process is as follows:

[0081] In(NO3)3+GaCl3+[(CH3)3Si]2NLi(LiHMDS)→InGaN+2(CH3)3SiCl+LiCl

[0082] like Figure 5 As shown, the peak at 505nm is the PL data of 50% indium-doped gallium nitride quantum dots.

[0083] 2) A silicon column template was prepared by photolithography, with a single silicon column having a width of 2 μm and a spacing of 16 μm. FAS modification was used to make the sidewalls of the silicon column template hydrophobic and the top hydrophilic.

[0084] 3) 15 μL of 100 mg / mL indium-doped gallium nitride quantum dot n-hexane dispersion was added to the surface of the silicon pillar template, covered with a silicon wafer substrate, and the entire template induction device was placed at room temperature to allow the solvent to evaporate naturally. After evaporation, an indium gallium nitride quantum dot superlattice array was obtained.

[0085] 4) Without disassembling the device of the above steps, the unpeeled indium-doped gallium nitride quantum dot superlattice array with silicon pillar template is placed in a tubular furnace filled with nitrogen atmosphere, and the temperature is raised to 950°C at 10°C / min and kept at this temperature for 45 minutes. The indium-doped gallium nitride quantum dots in the array gradually fuse, and finally the temperature is cooled to room temperature at 5°C / min.

[0086] 5) The template is peeled off from the substrate to obtain an indium-doped gallium nitride pattern having the same shape as the micro-pillar template on the silicon wafer substrate.

[0087] Example 4

[0088] like Figure 1a-1b As shown, a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting comprises the following steps:

[0089] 1) Synthesis of zinc-doped (25%) gallium nitride colloidal quantum dots. Under anhydrous and oxygen-free conditions, 5 mL of octadecene was placed in a three-necked flask and vacuum degassed for 2 h to remove water and oxygen in the solvent. 0.5 mmol of anhydrous gallium chloride, 0.17 mmol of zinc stearate and 1.5 mmol of stearic acid were added to the three-necked flask and vacuum degassed for 2 h while stirring and dissolving. After heating to 280 ° C at 10 ° C / min, 1 mL of 1.5 M lithium bis (trimethylsilyl) amide in n-hexane solution was quickly injected into the three-necked flask, and the reaction was continued for 60 min by heating and stirring. The heat source was removed and cooled with ice water to quench the reaction. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 min, the supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 min, the white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 min, and n-hexane and ethanol were added to wash twice, and finally the obtained white precipitate was dispersed in n-hexane;

[0090] The synthesis process is as follows Figure 2 As shown, the reaction process is as follows:

[0091] C 36 H7O4Zn+GaCl3+[(CH3)3Si]2NLi(LiHMDS)→ZnGaN+2(CH3)3SiCl+LiCl

[0092] like Figure 5 As shown, the peak at 414nm is the PL data of 25% zinc-doped gallium nitride quantum dots.

[0093] 2) A silicon column template was prepared by photolithography, with a single silicon column having a width of 2 μm and a spacing of 16 μm. FAS modification was used to make the sidewalls of the silicon column template hydrophobic and the top hydrophilic.

[0094] 3) 15 μL of 100 mg / mL zinc-doped gallium nitride quantum dot n-hexane dispersion was added to the surface of the silicon pillar template, covered with a silicon wafer substrate, and the entire template induction device was placed at room temperature to allow the solvent to evaporate naturally. After evaporation, a zinc-doped gallium nitride quantum dot superlattice array was obtained.

[0095] 4) Without disassembling the device of the above steps, the unpeeled zinc-doped gallium nitride quantum dot superlattice array with silicon pillar template is placed in a tubular furnace filled with nitrogen atmosphere, and the temperature is raised to 980°C at 10°C / min and kept at this temperature for 90 minutes. The zinc-doped gallium nitride quantum dots in the array gradually fuse, and finally the temperature is lowered to room temperature at 5°C / min.

[0096] 5) peeling the template from the substrate to obtain a zinc-doped gallium nitride pattern having the same shape as the micro-pillar template on the silicon wafer substrate;

[0097] Scanning electron microscopy and energy spectrum data such as Fig.13 As shown, the array has uniform morphology, high order, and accurate position. The energy spectrum data shows that the elements are evenly distributed and zinc is successfully doped.

[0098] Example 5

[0099] like Figure 1a-1b As shown, a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting comprises the following steps:

[0100] 1) Synthesis of zinc-doped (50%) gallium nitride colloidal quantum dots. Under anhydrous and oxygen-free conditions, 5 mL of octadecene was placed in a three-necked flask and vacuum degassed for 2 h to remove water and oxygen in the solvent. 0.5 mmol of anhydrous gallium chloride, 0.5 mmol of zinc stearate and 1.5 mmol of stearic acid were added to the three-necked flask and vacuum degassed for 2 h while stirring and dissolving. After heating to 280 ° C at 10 ° C / min, 1 mL of 1.5 M lithium bis (trimethylsilyl) amide in n-hexane solution was quickly injected into the three-necked flask, and the reaction was continued for 60 min by heating and stirring. The heat source was removed and the reaction was quenched by cooling with ice water. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 min. The supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 min. The white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 min. The n-hexane and ethanol were added and washed twice, and finally the obtained white precipitate was dispersed in n-hexane.

[0101] The synthesis process is as follows Figure 2 As shown, the reaction process is as follows:

[0102] C 36 H 70 Zn+GaCl3+[(CH3)3Si]2NLi(LiHMDS)→ZnGaN+2(CH3)3SiCl+LiCl

[0103] like Figure 5 As shown, the peak at 445nm is the PL data of 50% zinc-doped gallium nitride quantum dots.

[0104] 2) A silicon column template was prepared by photolithography, with a single silicon column having a width of 2 μm and a spacing of 16 μm. FAS modification was used to make the sidewalls of the silicon column template hydrophobic and the top hydrophilic.

[0105] 3) 15 μL of 100 mg / mL zinc-doped gallium nitride quantum dot n-hexane dispersion was added to the surface of the silicon pillar template, covered with a silicon wafer substrate, and the entire template induction device was placed at room temperature to allow the solvent to evaporate naturally. After evaporation, a zinc-doped gallium nitride quantum dot superlattice array was obtained.

[0106] 4) Without disassembling the device of the above steps, the unpeeled zinc-doped gallium nitride quantum dot superlattice array with silicon pillar template is placed in a tubular furnace filled with nitrogen atmosphere, and the temperature is raised to 980°C at 10°C / min and kept at this temperature for 90 minutes. The zinc-doped gallium nitride quantum dots in the array gradually fuse, and finally the temperature is lowered to room temperature at 5°C / min.

[0107] 5) The template is peeled off from the substrate to obtain a zinc-doped gallium nitride pattern having the same shape as the micro-pillar template on the silicon wafer substrate.

[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting, characterized in that: The following steps are involved: S1. Add a solvent, anhydrous gallium chloride and an organic ligand into a three-necked flask for vacuum degassing, heat the mixture using a liquid phase assembly drying device, inject a nitrogen source into the three-necked flask to obtain gallium nitride quantum dots, and then wash the mixture with a dispersion solvent to obtain a liquid phase assembled gallium nitride quantum dot dispersion; S2, preparing a silicon column template by photolithography, wherein the silicon column sidewalls of the silicon column template are hydrophobic and the top surface is hydrophilic; S3, dropping the liquid-phase assembled gallium nitride quantum dot dispersion onto the surface of the silicon pillar template, and covering the surface of the silicon pillar template with a substrate to obtain a template induction device, and placing the template induction device at room temperature to evaporate the dispersion solvent in the liquid-phase assembled gallium nitride quantum dot dispersion to obtain a gallium nitride quantum dot superlattice array; S4, placing the GaN quantum dot superlattice array in a high-temperature melting device filled with nitrogen atmosphere to increase the temperature to carbonize and decompose the organic ligands, and fuse the GaN quantum dots in the GaN quantum dot superlattice array, and then cooling to room temperature; S5. Peeling the silicon pillar template off the substrate, obtaining a gallium nitride single crystal pattern on the substrate with the same shape as the micro-pillar template, and completing a method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting.

2. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 1, characterized in that: In step S1, the solvent is octadecene, the organic ligand is stearic acid, the nitrogen source is a n-hexane solution of lithium bis(trimethylsilyl)amide, and the dispersion solvent is n-hexane or n-octane or acetone; The three-necked flask used an argon atmosphere and was placed in an anhydrous and oxygen-free device, which was a glove box and a double-row tube.

3. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 2, characterized in that: Octadecene is placed in a three-necked flask under anhydrous and oxygen-free condition, and then anhydrous gallium chloride and an organic ligand are added for vacuum degassing, and vacuum degassing is continued while stirring and dissolving. After heating, a n-hexane solution of lithium bis(trimethylsilyl)amide is injected, and heating and stirring are continued to react until the reaction is complete, the heat source is removed, and the reaction is quenched; after the temperature is restored to room temperature, the dispersion solvent is added, centrifuged, the supernatant is taken, the dispersion solvent is added again, and centrifuged again to obtain a white precipitate, which is gallium nitride quantum dots including ligands. The white precipitate is dispersed in the dispersion solvent, washed, and then dispersed in the dispersion solvent to obtain the liquid-phase assembled gallium nitride quantum dot dispersion.

4. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 1, characterized in that: In step S1, indium or zinc is doped into the gallium nitride quantum dots by adding indium salt or zinc salt into the three-necked flask, and the band gap is adjusted by adjusting the ratio of the added indium salt or zinc salt.

5. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 2, characterized in that: In step S1, 5-10 mL of octadecene is placed in a three-necked flask under anhydrous and oxygen-free conditions, and vacuum degassing is performed for 2 h to remove water and oxygen in the solvent. 0.5-1.0 mmol of anhydrous gallium chloride and 1.5-3.0 mmol of stearic acid are added to the three-necked flask, and vacuum degassing is continued for 2 h while stirring and dissolving. After heating to 220-300 ° C at 10 ° C / min, 1-2 mL of 1.5 M lithium bistrimethylsilylamide in n-hexane solution is quickly injected into the three-necked flask, and the heating and stirring reaction is continued for 10-100 min, the heat source is removed, and the reaction is cooled with ice water to quench the reaction. After the temperature returned to room temperature, the obtained liquid was added with n-hexane and centrifuged at 8000 rpm for 3 minutes. The supernatant was taken and acetone was added and centrifuged at 9000 rpm for 3 minutes. The white precipitate was dispersed in n-hexane and ethanol was added and centrifuged at 9000 rpm for 3 minutes. The n-hexane and ethanol were added and washed twice. Finally, the obtained white precipitate was dispersed in n-hexane to obtain a n-hexane dispersion of gallium nitride quantum dots.

6. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 5, characterized in that: In step S1, 0.5-1.0 mmol anhydrous gallium chloride, 0.1-0.5 mmol indium nitrate and 1.5-3.0 mmol stearic acid are added to a three-necked flask, step S1 obtains an indium-doped gallium nitride quantum dot n-hexane dispersion, step S3 obtains an indium-doped gallium nitride quantum dot superlattice array, and step S5 obtains an indium-doped gallium nitride pattern.

7. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 5, characterized in that: In step S1, 0.5-1.0 mmol anhydrous gallium chloride, 0.1-0.5 mmol zinc stearate and 1.5-3.0 mmol stearic acid are added to a three-necked flask, step S1 obtains a zinc-doped gallium nitride quantum dot n-hexane dispersion, step S3 obtains a zinc-doped gallium nitride quantum dot superlattice array, and step S5 obtains a zinc-doped gallium nitride pattern.

8. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 1, characterized in that: In step S2, the silicon pillars of the silicon pillar template have a spacing of 1-100 μm, a width of 1-100 μm, and a height of 10-100 μm. The silicon pillars are in the shape of a straight line, a rectangle, a triangle, or a ring, and are arranged in an array.

9. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 1, characterized in that: In step S3, the substrate is any one of the following: silicon wafer, sapphire, quartz wafer, silicon dioxide wafer, gold wafer, silver wafer and platinum wafer. Before use, the substrate is ultrasonicated in deionized water, ethanol, acetone and isopropanol for 20 minutes respectively, and dried with nitrogen for later use; The volume of the liquid-phase assembled gallium nitride quantum dot dispersion is 5-20 μL, and the evaporation temperature range is: 20-60°C.

10. The method for preparing a bandgap adjustable gallium nitride array based on quantum dot melting according to claim 1, characterized in that: In step S4, without disassembling the template induction device, the gallium nitride quantum dot superlattice array is placed in a high-temperature melting device filled with nitrogen atmosphere, the temperature is raised to 900-1100° C. at 10° C. / min, kept at this temperature for 60-90 min, and finally cooled to room temperature at 5° C. / min; The liquid phase assembly drying device and the high temperature melting device are any one of the following: a heating sheet, a heating plate, a vacuum oven and a tubular furnace.